A systematic approach of chitosan nanoparticle preparation via emulsion crosslinking as potential adsorbent in wastewater treatment. (15th January 2018) - Riegger, Benjamin R.; Bäurer, Bernd; Mirzayeva, Aziza; Tovar, Günter E.M.; Bach, Monika
Highlights: Synthesis of narrowly distributed crosslinked nanoparticles of different chitosans. Emulsion stability and particle yield increased by adding a hydrophile. Particle size depends on chitosan molecular weight. Adsorption of Diclofenac increases with decreasing nanoparticle particle size. Abstract: This study investigates the impact of glutaraldehyde (glut) concentration and molecular weight (MW) of six commercially available, highly deacetylated chitosans (Chi) on nanoparticle (Chi-NP) formation by emulsion crosslinking technique and their use as potential adsorber for diclofenac (DCL) and carbamazepine (CBZ). With a glut:primary amine ratio of 1:1 and NaCl as a hydrophile, it was possible to reproducibly synthesize narrowly distributed, spherical Chi-NPs over a broad range of chitosan MW with a high yield. Increasing Chi MW resulted in larger particle sizes ranging from 109.9 nm, for lowest MW, up to 200.3 nm for the highest MW, measured by DLS. To evaluate the static adsorption behavior of the Chi-NPs, CBZ and DCL were used in single point adsorption experiments. An adsorption capacity of up to 351.8 mg g −1 DCL for low MW Chi-NPs was observed and all Chi-NPs showed superior adsorptions when compared to untreated Chi.